The Effect of the Thai Herbal Suksaiyad Formula on Platelet Aggregation in Healthy Volunteers: A Quasi-experimental, Single-dose Study - Palo, Titchaphorn; Nathananwanit, Nalinthika; Akarasereenont, Pravit; Booranasubkajorn, Suksalin (Siriraj Medical Journal, 2025)
Objective: To investigate the effects of the Thai Herbal Suksaiyad formula (SSF) on platelet aggregation in healthy volunteers. Material and Methods: In a quasi-experimental study, thirty healthy volunteers received a single dose of 2,000 mg SSF. Blood samples were taken at 0, 3, 6, and 24 hours after SSF administration for platelet aggregation analysis using aggregometry. Platelets were induced with epinephrine, adenosine diphosphate, and collagen. Results: SSF significantly decreased platelet aggregation at 3 and 6 hours post-administration. Sub-analysis revealed no significant differences between males and females. SSF significantly decreased platelet aggregation in normal and hyperaggregation groups but had no effect on the disaggregation group. The effect of SSF was short-lived, reverting to pre-dose values after 24 hours for all agonists. Adverse events included flatulence (1 participant) and diarrhea (1 participant). Conclusion: Caution is advised when using SSF in patients with blood disorders. Potential herb-drug interactions between SSF and drugs that impact platelet aggregation, such as aspirin, should be closely monitored. These interactions could result in fluctuations that may enhance or diminish the effectiveness of concurrent antiplatelet therapies, potentially increasing the risk of bleeding or decreasing therapeutic outcomes.